The A to Z of corporate social responsibility : a complete reference guide to concepts, codes and organisations - Visser, Wayne (Chichester, England ; Hoboken, NJ : John Wiley & Sons, 2007)
This is the world's first complete reference on CSR. The entries have been written by leading experts, leading global thinkers and CSR practitioners. In these pages lie the answers to questions such as: What do we mean by CSR? In what way are organizations viewed as citizens of the countries in which they operate? How does a company know when it is operating in a sustainable way? What is ethical investment? The reference also lists and describes the most important organizations and landmarks in the field of CSR.
THE A TO Z OF CORPORATE SOCIAL RESPONSIBILITY; CONTENTS; FOREWORD; THE A TO Z OF CSR -- INTRODUCTION; ABOUT THE EDITORS; LIST OF CONTRIBUTORS; CONTENTS OF THE A TO Z; THE A TO Z; LIST OF ABBREVIATIONS; INDEX OF TERMS.
Includes index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Includes bibliographical references and index.
English.
Keywords: Social responsibility of business; Entreprises; BUSINESS & ECONOMICS -- Development -- Sustainable Development; Social responsibility of business; Soziale Verantwortung; Unternehmen; Electronic books; 2